Using pRIFLE criteria for acute kidney injury in critically ill children - Rina Amalia C. Saragih; Jose M. Mandei; Irene Yuniar; Rismala Dewi; Sudung O. Pardede; Antonius Pudjiadi; Abdul Latief (Indonesian Pediatric Society Publishing House, 2013)
Backgi-ound Incidence of acute kidney injury (AKI) in critically ill children and its mortality rate is high. The lack of a uniform definition for AKI leads to failure in determining kidney injury, delayed treatment, and the inability to generalize research results. Objectives To evaluate the pediatric RIFLE (pRIFLE) criteria (risk for renal dysfunction, injury to the kidney, failure of kidney function, loss of kidney function, and end-stage renal disease) for diagnosing and following the clinical course of AKI in critically ill children. We also aimed to compare AKI severity on days 1 and 3 of pediatric intensive care unit (PICU) stay in critically ill pediatric patients. Methods This prospective cohort study was performed in PICU patients. Urine output (UOP), serum creatinine (SCr) , and glomerular filtration rate on days 1 and 3 of PICU stay were recorded. Classification of AKI was determined according to pRIFLE criteria. We also recorded subjects' immune status, pediatric logistic organ dysfunction (PELOD) score, admission diagnosis, the use of vasoactive medications, diuretics, and ventilators, as well as PICU length of stay and mortality. Results Forty patients were enrolled in this study. AKI was found in 13 patients (33%). A comparison of AKI severity on day 1 and day 3 revealed no statistically significant differences for attainment of pRIFLE criteria by urine output only (pRIFLfu0 p; P=0.087) and by both UOP and SCr (pRIFLEcr+uo p; P= 0.577). However, attainment of pRIFLE criteria by SCr only (pRIFLEcrl was significantly improved between days 1 and 3 (P =0.026). There was no statistically significant difference in mortality or length of stay between subjects with AKI and those without AKI. Conclusion The pRIFLE criteria is feasible for use in diagnosing and following the clinical course of AKI in critically ill children.